Leaking the secret: women's attitudes toward menstruation and menstrual-tracker mobile apps - Thompson, Sydney Elizabeth, author; Sivakumar, Gayathri, advisor; Martey, Rosa Mikeal, committee member; Griffin, Cindy, committee member (Colorado State University. Libraries, 2016)
This study explored how menstrual-tracker mobile apps have characteristics that reflect menstruation as a taboo in the U.S. culture. Objectification theory and gender schema theory provided a conceptual and overarching framework to explore how the U.S. sociocultural context may play a role in the development of norms and assumptions surrounding menstruation, and in turn, menstrual-tracker mobile apps reflecting society’s norms and assumptions about menstruation as a taboo. Feminist theory is discussed as well, as it shed light on the development of the androcentric view toward menstruation in the United States, and it kindled the researcher’s interest in conducting this study. A dearth of literature exists about menstrual-tracker mobile apps as cultural products, and an online survey was conducted among a convenience sample of female undergraduate millennials (n = 258) to investigate if a correlation exists between their attitudes toward menstruation as a taboo and menstrual-tracker mobile apps’ security features, body control features, and discussion features. The analysis of the data revealed that female undergraduate millennials’ attitudes toward menstruation as a taboo in this study correlated to their attitudes toward security features and discussion features but not body control features on menstrual-tracker mobile apps.